Practice guideline: joint CCMG-SOGC recommendations for the use of chromosomal microarray analysis for prenatal diagnosis and assessment of fetal loss in Canada. Issue 4 (1st March 2018) - Armour, Christine M; Dougan, Shelley Danielle; Brock, Jo-Ann; Chari, Radha; Chodirker, Bernie N; DeBie, Isabelle; Evans, Jane A; Gibson, William T; Kolomietz, Elena; Nelson, Tanya N; Tihy, Frédérique; Thomas, Mary Ann; et al.
Abstract : Background: The aim of this guideline is to provide updated recommendations for Canadian genetic counsellors, medical geneticists, maternal fetal medicine specialists, clinical laboratory geneticists and other practitioners regarding the use of chromosomal microarray analysis (CMA) for prenatal diagnosis. This guideline replaces the 2011 Society of Obstetricians and Gynaecologists of Canada (SOGC)-Canadian College of Medical Geneticists (CCMG) Joint Technical Update. Methods: A multidisciplinary group consisting of medical geneticists, genetic counsellors, maternal fetal medicine specialists and clinical laboratory geneticists was assembled to review existing literature and guidelines for use of CMA in prenatal care and to make recommendations relevant to the Canadian context. The statement was circulated for comment to the CCMG membership-at-large for feedback and, following incorporation of feedback, was approved by the CCMG Board of Directors on 5 June 2017 and the SOGC Board of Directors on 19 June 2017. Results and conclusions: Recommendations include but are not limited to: (1) CMA should be offered following a normal rapid aneuploidy screen when multiple fetal malformations are detected (II-1A) or for nuchal translucency (NT) ≥3.5 mm (II-2B) (recommendation 1); (2) a professional with expertise in prenatal chromosomal microarray analysis should provide genetic counselling to obtain informed consent, discuss the limitations of the methodology, obtain the parental decisions for return of incidental findings (II-2A) (recommendation 4) and provide post-test counselling for reporting of test results (III-A) (recommendation 9); (3) the resolution of chromosomal microarray analysis should be similar to postnatal microarray platforms to ensure small pathogenic variants are detected. To minimise the reporting of uncertain findings, it is recommended that variants of unknown significance (VOUS) smaller than 500 Kb deletion or 1 Mb duplication not be routinely reported in the prenatal context. Additionally, VOUS above these cut-offs should only be reported if there is significant supporting evidence that deletion or duplication of the region may be pathogenic (III-B) (recommendation 5); (4) secondary findings associated with a medically actionable disorder with childhood onset should be reported, whereas variants associated with adult-onset conditions should not be reported unless requested by the parents or disclosure can prevent serious harm to family members (III-A) (recommendation 8). The working group recognises that there is variability across Canada in delivery of prenatal testing, and these recommendations were developed to promote consistency and provide a minimum standard for all provinces and territories across the country (recommendation 9).